Prevalence of aggressive or violent behaviour in Thai patients with schizophrenia: A cross-sectional study - N. Maneeton (2020)
© 2019 Hong Kong Academy of Medicine Press. All rights reserved. Objective: This study aimed to determine the prevalence of violence and factors associated with aggressive or violent behaviour in Thai patients with schizophrenia. Methods: This cross-sectional study was conducted in all patients with schizophrenia aged £18 years admitted to Suan Prung Psychiatric Hospital, Thailand, between January and November 2014. Baseline interviews were conducted by a psychiatrist and psychiatric nurses. Accessibility to weapons and toxic chemicals was evaluated. Results: Of 230 patients with schizophrenia screened, 207 (162 men and 45 women) were included. Of them, only 16 (7.7%) patients had aggressive or violent behaviour, including verbal aggression (n = 7), physical aggression (n = 5), and aggression against property (n = 4). Nonetheless, only 2 (12.5%) of them had been chargcd by the police. The weapon score was higher in violent than non-violent patients (p < 0.05). Binary logistic regression analysis showed that the weapon score was the only significant predictor of violence. Conclusion: Patients with schizophrenia with greater access to weapons were more likely to have aggressive or violent behaviour. Routine screening for access to weapons in clinical settings and adequate treatment of psychotic symptoms may reduce the incidence of aggressive or violent behaviour and violent offences.